The impact of representative employee participation on work environment quality and business outcomes in the hotel industry - Markey, R; Harris, C; Lamm, F; Williamson, D; Lind, J; Busck, O; Knudsen, H (International Industrial Relations Association (IIRA), 2009)
The paper evaluates the impact of representative employee participation on the work environment and business outcomes in the hotel industry in De nmark and New Zealand (NZ). These countries are of similar population and economic structure. Each has legislation for occupational health and safety (OHS) delegates, but in NZ this is quite recent and wider participative practices are not well developed by employer/union agreement as in Denmark with co operation committees. Comparison between the two countries enables testing of the impact of the degree of embeddedness of participative practices.